Discussion and Think-Pair-Share Strategies on the Enhancement of EFL Students’ Speaking Skill: Does Critical Thinking Matter? - Annisaa Eka Warliati; Zainal Rafli; Darmahusni Darmahusni (English Department - University of Sultan Ageng Tirtayasa, 2019)
Previous research has underscored the importance of learning strategies and critical thinking. However, the relationship between both constructs toward the enhancement of the students’ speaking skills in EFL context still receives scant attention. Therefore, this study aims to investigate the influence of learning strategies (i.e. Discussion Strategy and Think-Pair-Share Strategy/TPS) mediated by critical thinking on the speaking skill of the Department of English Education students at a private university in Cirebon. The subject of this research consisted of 60 students divided into two classes (N=30 for experimental class and N=30 for control class). This study employed an experimental research design with a 2X2 factorial design. The findings demonstrated that English speaking skill of the students with Discussion Strategy was higher than those with the TPS strategy. Second, the English speaking skill of the students with high critical thinking level was higher than those with low critical thinking level. Third, there was a relationship between learning strategy and critical thinking toward English speaking skill. Fourth, there was no significant difference between the students’ speaking skills with Discussion strategy than those with Think-Pair-Share strategies in the group of students with low critical thinking level. This study concludes with the recommendations for future research to examine the effectiveness of discussion and think-pair-share strategies on enhancing the students’ critical thinking skills to promote their speaking skills.